ANÁLISE DA APLICAÇÃO DO MODELO LEAN CONSTRUCTION EM CANTEIROS DE OBRAS RODOVIÁRIAS: ESTUDO DE CAMPO EM TRECHO DA BR 158 - Oroski, Taíme da Cruz; Pereira Filho, José Ilo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Civil constrution is a fundamental sector in society's daily life. However, its technical and technological development happens at a much lower intensity than that seen in other sectors. The result of this is a decrease in the productivity of its services and a compromise of its products quality. Since both the movement of people and the transportation of cargoes are still done mostly through highways, it is important to develop road works with quality, safety and efficiency. In this sense, the adoption of management models can be very beneficial. This work focuses on the use of the management model called Lean Construction which aims to reduce losses in production. On the field study in the BR 158 works some activities were observed and lean principles already adopted at the site were identified. Posteriorly, lean improvements were suggested. Finally the viability of the lean mentality use in a formal way in this type of work was evaluated. A great potential was detected, since many of the lean principles were identified even if in an unintentional way. However, it was verified that for the full adoption of the management model, a diffusion of the knowledge related to the topic is necessary.